"Sustainability in the Planning of Residential Complexes (A Case Study: Al Ghadeer Village Residential Investment in Najaf)" (Journal of Planner and Development, 2024)
Abstract: The concept of sustainability has emerged as a solution to many problems facing cities, and it has become essential to follow in various fields and sectors, particularly the housing sector due to its significant economic and social importance. Therefore, it is necessary to understand the nature of sustainability and how to achieve it in the planning of residential complexes. This requires identifying effective and integrated criteria and indicators that serve this purpose. The Al Ghadeer Residential Village was chosen as one of the residential investment projects witnessed by the city of Najaf in recent times. However, there is dissatisfaction with some effective indicators in achieving sustainability in the studied residential complex. Applying sustainability criteria and indicators in the planning of residential complexes contributes to creating housing projects that are suitable from all social, economic, and environmental aspects. The study adopted a descriptive approach and obtained residents’ opinions through a questionnaire designed to identify the most prominent criteria and indicators and assess residents’ satisfaction with them. The sample size was 60 questionnaires distributed to residential units, and a set of conclusions was reached, including the following: Most of the urban criteria related to the residential environment in the study area comply with national standards except for the criteria related to the adequacy of educational, health, and commercial services for the population. Residents are dissatisfied with the social indicators related to privacy, the lack of green and open spaces, play areas for children, and the unavailability of public transportation within the vicinity of the residential complex